Nationwide Incidence and Outcomes of Patients With Coronavirus Disease 2019 Requiring Intensive Care in Iceland - Kristinsson, Bjarki (Crit Care Med, 2020)
To determine the nationwide demographics and hospital mortality of patients with severe acute respiratory syndrome coronavirus 2 infection requiring admission to the ICU for coronavirus disease 2019 in Iceland. DESIGN: Prospective observational study. SETTING: All ICUs in Iceland (Landspitali University Hospital and Akureyri Regional Hospital). PATIENTS: All patients admitted to the ICU for management of coronavirus disease 2019 between March 14, 2020, and April 13, 2020, with follow-up through May 5, 2020. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: A total of 27 patients were admitted to the ICU for coronavirus disease 2019 out of 1,788 severe acute respiratory syndrome coronavirus 2 positive cases, rendering an overall admission ratio of 1.5% (95% CI, 1.0–2.2%). The population rate of ICU admission for coronavirus disease 2019 was 7.4 (95% CI, 4.9–10.8) admissions per 100,000 individuals. The hospital mortality of patients admitted to the ICU was 15% (95% CI, 4–34%), and the mortality of patients receiving mechanical ventilation was 19% (95% CI, 4–46%). CONCLUSIONS: We report a lower overall ratio of ICU admissions for coronavirus disease 2019 among severe acute respiratory syndrome coronavirus 2 positive patients and a lower hospital mortality for patients treated in the ICU for coronavirus disease 2019 compared with initial reports from Italy and China. Our results could be explained by the early adoption of widespread testing and a successful national response to the pandemic.